Adventures in Eating : Anthropological Experiences in Dining from Around the World - Sammells, Clare A., 1973-; Haines, Helen R. (Book collections on Project MUSE., 2010)
"Anthropologists training to do fieldwork in far-off, unfamiliar places prepare for significant challenges with regard to language, customs, and other cultural differences. However, like other travelers to unknown places, they are often unprepared to deal with the most basic and necessary requirement: food. Although there are many books on the anthropology of food, Adventures in Eating is the first intended to prepare students for the uncomfortable dining situations they may encounter over the course of their careers." "Many cultures place significance on food and hospitality, and whether sago grubs, jungle rats, termites, or the pungent durian fruit are on the table, participating in the act of sharing food can establish relationships vital to anthropologists' research practices and knowledge of their host cultures. Using their own experiences with unfamiliarand sometimes unappealingfood practices and customs, the contributors explore such eating moments and how these moments can produce new under-standings of culture and the meaning of food beyond the immediate experience of eating it. They also address how personal eating experiences arid culinary dilemmas can shape the data and methodologies of the discipline." "The main readership of Adventures in Eating will be students in anthropology and other scholars, but the explosion of food media gives the book additional appeal for fans of No Reservations and Bizarre Foods on the Travel Channel." "Helen R. Haines is a research associate at Trent University Archaeology Research Center and teaches anthropology at Trent University and the University of Toronto-Mississauga." "Clare A. Sammells is assistant professor of anthropology at Bucknell University."--Jacket.